2001
DOI: 10.1002/1529-0131(200101)44:1<176::aid-anr23>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association between interleukin-10 promoter region polymorphisms and primary Sj�gren's syndrome

Abstract: Objective To determine whether the haplotypes formed on the basis of single‐base–exchange polymorphisms at positions −1082, −819, or −592 of the interleukin‐10 (IL‐10) gene predispose subjects to primary Sjögren's syndrome (SS). Methods The frequency of IL‐10 polymorphisms was analyzed in 62 patients with primary SS and in 400 healthy subjects. These data were assessed for correlations with the concentration of IL‐10 in the plasma. Results The frequency of the IL‐10 GCC haplotype (G at position −1082, C at pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
2
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 15 publications
(29 reference statements)
2
46
2
1
Order By: Relevance
“…Rischmueller et al (15) found no association with primary SS in a study involving 108 Australian patients. Conversely, Hulkonnen et al (16) and Font et al (17) reported that the GCC allele frequency and haplotype carrier rate were significantly 578 GOTTENBERG ET AL increased and the ACC frequency decreased in 62 Finnish SS patients and 63 Spanish SS patients, respectively. Despite the biologic effect of IL-10 on immunoglobulin and autoantibody synthesis (39), its polymorphisms were not associated with levels of serum immunoglobulins or with the pattern of secretion of autoantibodies in any of the 4 studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Rischmueller et al (15) found no association with primary SS in a study involving 108 Australian patients. Conversely, Hulkonnen et al (16) and Font et al (17) reported that the GCC allele frequency and haplotype carrier rate were significantly 578 GOTTENBERG ET AL increased and the ACC frequency decreased in 62 Finnish SS patients and 63 Spanish SS patients, respectively. Despite the biologic effect of IL-10 on immunoglobulin and autoantibody synthesis (39), its polymorphisms were not associated with levels of serum immunoglobulins or with the pattern of secretion of autoantibodies in any of the 4 studies.…”
Section: Discussionmentioning
confidence: 97%
“…The constitutive expression of TNF␣, TGF␤1, IL-10, IL-6, and IFN␥ has been reported to be influenced by functional polymorphisms in their gene loci (10)(11)(12)(13)(14), thus providing a rationale for the study of their potential role in susceptibility to primary SS. However, studies of cytokine polymorphisms, which are limited in primary SS, have often involved a small number of patients, and the results of IL-10 polymorphism studies remain a subject of controversy (15)(16)(17)(18)(19)(20). Moreover, the role of TGF␤1 has never been investigated in any genetic study in SS.…”
mentioning
confidence: 99%
“…Based on this survey, IL-10 could not be considered as a primary factor in the development of primary SS [70]. As opposed to this, a recent study described an association between primary SS and IL-10 promoter polymorphisms in a cohort of Finnish individuals [71]. This report suggested that the GCC/GCC or the GCC/ATA genotype of the IL-10 promoter was associated with increased susceptibility to pSS.…”
Section: Il-10mentioning
confidence: 95%
“…This report suggested that the GCC/GCC or the GCC/ATA genotype of the IL-10 promoter was associated with increased susceptibility to pSS. Furthermore, the levels of circulating IL-10 were measured and the GCC haplotype was found correlated with high plasma levels of IL-10 in primary SS [71].…”
Section: Il-10mentioning
confidence: 99%
“…[12][13][14][15] A number of studies have been presented providing evidence for associations between these IL-10 promoter variants and infectious or autoimmune diseases, including meningococcal infection, fatal septicemia, systemic lupus erythematodes, reactive arthritis, psoriasis, Sjogreń s syndrome, and multiple sclerosis. 10,12,[16][17][18][19][20] So far, it has not been studied, however, whether IL-10 promoter variants influence lymphocyte proliferation upon antigen stimulation, a major regulatory function attributed to IL-10.…”
Section: Introductionmentioning
confidence: 99%